2008
DOI: 10.1007/s12306-007-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted alignment system for tibial component placement in total knee replacement: a radiological study

Abstract: In total knee replacement (TKR), regarding tibial component positioning, almost all implants offer both an intramedullary and an extramedullary alignment guide, leaving it up to the surgeon which guide to use. However, early failure in TKR can be caused by incorrect positioning or orientation with poor limb alignment. Recently computer-based alignment systems have been developed to help the surgeon to overcome these complications. The Authors retrospectively analysed their experience using a computer-based CT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Even with the use of manual instrumentation and navigation, studies have shown that surgeons may not always achieve optimal alignment. [9][10][11][12][13][18][19][20]40 Therefore, this study assessed RATKA, which has been introduced to potentially minimize the margin of alignment error associated with component placement. The operating surgeon had over 25 years of manual TKA experience, and following a single cadaver training with no previous robotic experience, the surgeon's first six RATKA demonstrated greater accuracy and precision of bone cuts and component placement to plan, compared with MTKA in this cadaver study.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the use of manual instrumentation and navigation, studies have shown that surgeons may not always achieve optimal alignment. [9][10][11][12][13][18][19][20]40 Therefore, this study assessed RATKA, which has been introduced to potentially minimize the margin of alignment error associated with component placement. The operating surgeon had over 25 years of manual TKA experience, and following a single cadaver training with no previous robotic experience, the surgeon's first six RATKA demonstrated greater accuracy and precision of bone cuts and component placement to plan, compared with MTKA in this cadaver study.…”
Section: Discussionmentioning
confidence: 99%
“…However, reported advantages of CAS techniques are the immediate, intraoperative feedback provided, and the reduction in outliers in obese patients or patients with extra-articular deformities, in whom conventional IM or EM techniques may be inadequate [20]. Manzotti et al, in a review of 38 TKAs implanted using a CAS system, found 89.4% of tibial components to be aligned within 2°of perpendicular to the mechanical axis in the coronal plane, and 100% of components aligned within 4°o f the targeted value in the sagittal plane [21]. In addition, Pang et al, in a review of 35 TKAs implanted using a CAS system, found the mean postoperative coronal alignment to be 0.5°± 1.8°, and sagittal alignment to be 1.7°± 1.9°(goal 0°) [19].…”
Section: Tablementioning
confidence: 99%
“…The most commonly used method of setting coronal component alignment in TKA is an extramedullary tibial and an intramedullary femoral alignment guide, but this method has shown a limited degree of accuracy [2,3,5,21,30]. Although computer-assisted surgical techniques have consistently demonstrated improved alignment accuracy versus standard guides [3,13,16,19,27,32], the increased capital costs, operative times, learning curve, and unproven functional benefits associated with their use have limited their widespread acceptance [9].…”
Section: Introductionmentioning
confidence: 99%